FACTORS INFLUENCING THE POLITICIZATION OF RELIGION IN MODERN TIMES - Abrorjon Pulatov (International Scientific and Current Research Conferences, 2021)
Religion has always been an important factor affecting all aspects of society. The level of religiosity in the world is not decreasing, on the contrary, it is rising at the contemporary stage. After the two-polarization period, "we have to celebrate the return of traditionalism. " It primarily belongs to Islam.